The Comparison of Maternal and Child Health Research and Health Empowerment in Coastal Areas: A review - Febriana Muchtar; Elfirah; Rina Ariani (Journal of Health Science and Pharmacy, 2025)
Background: Maternal, infant, and child health in coastal areas is often affected by multiple interrelated factors, including limited knowledge of nutrition, inadequate practices of exclusive breastfeeding, and poor environmental sanitation. These determinants significantly contribute to health disparities in coastal communities. Addressing these challenges requires targeted interventions focusing on education and community empowerment. Objective: This study aims to examine the impact of educational interventions and community empowerment programs on improving maternal, infant, and child health outcomes in coastal areas. Method: The study implemented a series of intervention programs, including training sessions for Posyandu (integrated health post) cadres, educational counseling on exclusive breastfeeding, home visits for pregnant women, and initiatives aimed at improving environmental sanitation. Results: The findings demonstrate that nutritional education provided to Posyandu cadres significantly enhanced their understanding of stunting prevention. In addition, rates of exclusive breastfeeding increased in correlation with improved maternal awareness of its benefits. Home visit counseling proved effective in raising knowledge among pregnant women regarding anemia prevention. Poor sanitation was identified as a major contributing factor to the prevalence of stunting and respiratory tract infections (RTIs) among children. The empowerment of health cadres facilitated early detection of health problems and broadened access to primary healthcare services. Collectively, these educational, empowerment, and sanitation-based interventions led to measurable improvements in maternal and child health indicators within the targeted coastal communities. Conclusion: Interventions focused on education, community empowerment, and environmental sanitation improvement contribute positively to maternal, infant, and child health outcomes in coastal areas. Such integrative approaches are essential for achieving sustainable health improvements in underserved coastal populations. Keywords: Nutrition Education, Exclusive Breastfeeding, Stunting, Sanitation, Health Cadres, Pregnant Women, Community Empowerment